Atmospheric patterns driving Holocene productivity in the Alboran Sea (Western Mediterranean): A multiproxy approach. (April 2015) - Ausín, Blanca; Flores, Jose A; Sierro, Francisco J; Cacho, Isabel; Hernández-Almeida, Iván; Martrat, Belén; Grimalt, Joan O
High-resolution paleoproductivity variations have been reconstructed in a productive cell in the Alboran Sea for the Holocene. Fossil coccolithophore assemblages have been studied along with theU 37 K ′ -estimated sea-surface temperature (SST) and other paleoenvironmental proxies. The appearance of this cell is suggested at 7.7 ka cal. BP and was linked to the establishment of the western anti-cyclonic gyre. From that time until the present, the nannofossil accumulation rate of Florisphaera profunda has revealed successive episodes of weakening and strengthening of upwelling conditions in the Alboran Sea that have been simultaneous to changes in Western Mediterranean Deep Water (WMDW) formation in the Gulf of Lions. A two-phase scenario operating at millennial–centennial time scale is proposed to explain this climatic and oceanographic variability: (1) coeval with more arid climate conditions, weaker northerlies or north-westerlies blowing over the Gulf of Lions would have triggered a slackening of WMDW formation. This together with a minor Atlantic Jet (AJ) inflowing into the Alboran Sea would have led to less vertical mixing and, hence, a more stable water column in the study area; (2) wetter climate conditions would have prevailed in the region, while stronger northerlies or north-westerlies would have enabled WMDW reinforcement in the Gulf of Lions simultaneous to an intensification of the AJ that migrated southward. This would have increased vertical mixing, intensifying upwelling conditions in the study area. Here, the winter North Atlantic Oscillation (NAO) is considered to be an important forcing mechanism for this variability, influencing WMDW formation, which in turn has been linked to short-term productivity variations during the last 7.7 ka in the Alboran Sea.